First aid at school: teacher and staff training - Lucas Felix Calandrim; Adriana Breves dos Santos; Lais Rodrigues de Oliveira; Cleuza Aparecida Vedovato; Luciana Gonçalves Massaro; Ana Paula Boaventura (Rev Rene)
Objective: to evaluate the knowledge of teachers and employees after first aid training. Methods: this is a near pretest and post-test experiment for 35 staff and teachers of a school, evaluated using validated instruments for knowledge and skill in two stages, before and after a course/training. Results: 97.1% (34) female professionals participated, 42.8% (15) reported having received some training and 71.4% (25) had already witnessed an emergency case. Before the training, an average score of 19.43 referring to skill and 2.91 points in knowledge was verified and after 174.57 points in skill and 9.17 in knowledge, a statistically significant difference by the Wilcoxon Signal Station Test (p<0.001). Conclusion: training is effective, with a significant increase in the percentage of correct answers after first aid training in the school environment.